Effects of cold work on solute atom clustering during thermal aging in RPV model alloy. Issue 5 (4th May 2021) - Fujii, Katsuhiko; Fukuya, Koji
ABSTRACT: The effect of initial material strength induced by cold work on the formation of solute atom clusters was investigated for thermal-aged Fe-Cu alloy specimens with and without cold work to understand the effects of material properties before irradiation on radiation embrittlement in reactor pressure vessel (RPV) steels. The results of solute atom cluster analysis by atom probe tomography supported the idea that cold work enhances the mobility of solute atoms by the vacancies associated with dislocations that were generated by the cold work and influences the formation and growth of solute atom clusters. Formation and growth of solute atom clusters by cold work was greater for more hardening in the RPV model alloy with higher yield strength. Cold work would be expected to worsen irradiation hardening and embrittlement.